Acid secretion and sensitivity to gastrin in patients with duodenal ulcer: effect of eradication of Helicobacter pylori. Issue 7 (July 1993) - Moss, S F; Calam, J
Abstract : The effect of ulcer healing with eradication of Helicobacter pylori (H pylori) on gastric function was investigated in nine patients with duodenal ulcer disease. One month after eradication there were significant reductions in both basal plasma gastrin concentration, from a median (range) of 19 (1-22) to 6 (2-15) pmol/l (p < 0.05), and of basal acid secretion from 8.3 (2.4-24) to 2.6 (1.4-8.1) mM H+/h, (p < 0.01). The peak acid secretion rate was unchanged from 37 (16-59) to 37 (21-59) mM H+/h. After treatment there was no change in the parietal cell sensitivity to stepped infusions of gastrin heptadecapeptide: the median concentration of gastrin required for 50% of maximal acid secretion (EC50) was 41 (14.8-126) before and 33 (23-125) pmol/l after eradication of H pylori. The metabolic clearance rate of gastrin was also unaffected by the eradication of H pylori. Thus eradication of H pylori infection from patients with active duodenal ulcers is accompanied by falls in both basal gastrin release and basal acid secretion without a change in the parietal cell sensitivity to gastrin. Cyclical changes in H pylori infection may cause the variations in basal acid secretion that are seen in duodenal ulcer disease.